(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The technological advancement ensures the durability of the constructed roads in a cost friendly manner. The utilisation of soil additives, such as lime, cement, cement kiln dust, Ground Granulated Blast Furnace Slag (GGBS) Powder, Rice husk ash (RHA), limestone ash and asphalt, has become a prevalent technique for enhancing the geotechnical characteristics of substandard building materials, particularly expansive soils. The present study aims to examine the impact of (GGBS) Powder and rice husk ash on the engineering characteristics of black cotton soil (BCS). In this work, the strength of BCS has been examined by incorporating different concentration of GGBS and rice husk ash power for both soaked and unsoaked soil samples using California Bearing Ratio (CBR) test. The findings of the study suggested that the optimal combination of materials for achieving the highest soaked CBR value is a proportion of 10% Rice husk ash powder and 8% GGBS Powder when added to soil. Therefore, this ratio can be utilized in the construction of road pavements and embankments.